Dynamic interaction of poly(A)-binding protein with the ribosome. Issue 1 (December 2018) - Machida, Kodai; Shigeta, Tomoaki; Yamamoto, Yuki; Ito, Takuhiro; Svitkin, Yuri; Sonenberg, Nahum; Imataka, Hiroaki
Abstract Eukaryotic mRNA has a cap structure and a poly(A) tail at the 5′ and 3′ ends, respectively. The cap structure is recognized by eIF (eukaryotic translation initiation factor) 4 F, while the poly(A) tail is bound by poly(A)-binding protein (PABP). PABP has four RNA recognition motifs (RRM1–4), and RRM1-2 binds both the poly(A) tail and eIF4G component of eIF4F, resulting in enhancement of translation. Here, we show that PABP interacts with the 40S and 60S ribosomal subunits dynamically via RRM2-3 or RRM3-4. Using a reconstituted protein expression system, we demonstrate that wild-type PABP activates translation in a dose-dependent manner, while a PABP mutant that binds poly(A) RNA and eIF4G, but not the ribosome, fails to do so. From these results, functional significance of the interaction of PABP with the ribosome is discussed.